2020
DOI: 10.48550/arxiv.2011.01962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knots, links, and long-range magic

Jackson R. Fliss

Abstract: We study the extent to which knot and link states (that is, states in 3d Chern-Simons theory prepared by path integration on knot and link complements) can or cannot be described by stabilizer states. States which are not classical mixtures of stabilizer states are known as "magic states" and play a key role in quantum resource theory. By implementing a particular magic monotone known as the "mana" we quantify the magic of knot and link states. In particular, for SU (2) k Chern-Simons theory we show that knot … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…It would be of interest to investigate how our notion of complexity might be related to other geometric notions of complexity in that context. We note the recent related paper [31].…”
Section: Summary and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It would be of interest to investigate how our notion of complexity might be related to other geometric notions of complexity in that context. We note the recent related paper [31].…”
Section: Summary and Discussionmentioning
confidence: 94%
“…The order in (31) does not matter since their commutator is higher order. Comparing (30) and (31) we get…”
Section: The Path Of Minimal Complexitymentioning
confidence: 99%
“…Fliss [19] has studied knot and link states of SU(2) d Chern-Simons theory, and has shown that knot and link states are generically magical. However for U(1) d , magic is absent for all knot and link states.…”
Section: Discussionmentioning
confidence: 99%
“…However for U(1) d , magic is absent for all knot and link states. Since U(1) d is level-rank dual to SU(d) 1 , the knot and link states for this theory also have zero magic [19][20][21], [22].…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22]. Qudits also naturally arise in topological field theories -the Hilbert space of an SU (2) k Chern-Simons theory on a torus is k + 1-dimensional [23] -see, e.g., [24,25] for discussion related to quantum computing.…”
Section: Introductionmentioning
confidence: 99%